'Aeromonas intestinalis' and 'Aeromonas enterica' isolated from human faeces, 'Aeromonas crassostreae' from oyster and 'Aeromonas aquatilis' isolated from lake water represent novel species. (January 2017) - Figueras, M.J.; Latif-Eugenín, F.; Ballester, F.; Pujol, I.; Tena, D.; Berg, K.; Hossain, M.J.; Beaz-Hidalgo, R.; Liles, M.R.
Abstract: Four Aeromonas strains from clinical and environmental samples differed from known species on the basis of rpoD gene sequence. Multilocus phylogenetic analysis and in silico DNA-DNA hybridization confirmed them as four new species even though their 16S rRNA gene sequence similarity with their closest relatives was >98.7%, as occurred for other Aeromonas spp.